Use of Transposon-Transposase Systems for Stable Genetic Modification of Embryonic Stem Cells - Orbán, Tamás I.; Apáti, Ágota; Izsvák, Zsuzsanna; Ivics, Zoltán; Sarkadi, Balázs (IntechOpen, 2011)
None